Negotiating decisions on aggressive cancer care at end-of-life between patients, family members, and physicians: a qualitative interview study - Haun, Markus W.; Wildenauer, Alina; Hartmann, Mechthild; Bleyel, Caroline; Becker, Nikolaus; Jäger, Dirk; Friederich, Hans-Christoph; Tönnies, Justus (Frontiers in oncology, 2022)
BackgroundPatients with advanced cancer do receive increasingly aggressive end-of-life care, despite it does often not prolong survival time but entails decreased quality of life for patients. This qualitative study explores the unfolding of aggressive end-of-life care in clinical practice focusing on the decision-making process and the quality of end-of-life care from family members’ perspective.Materials and methodsWe conducted semi-structured interviews with 16 family members (six of cancer patients with and ten without aggressive end-of-life care) at the National Center for Tumor Diseases Heidelberg, Germany. We conducted a content analysis applying a theoretical framework to differentiate between ‘decision-making’ (process of deciding for one choice among many options) and ‘decision-taking’ (acting upon this choice).ResultsWhile patients of the aggressive care group tended to make and take decisions with their family members and physicians, patients of the other group took the decision against more aggressive treatment alone. Main reason for the decision in favor of aggressive care was the wish to spend more time with loved ones. Patients took decisions against aggressive care given the rapid decline in physical health and to spare relatives difficult decisions and arising feelings of guilt and self-reproach.ConclusionTreatment decisions at end-of-life are always individual. Nevertheless, treatment courses with aggressive end-of-life care and those without differ markedly. To account for a longitudinal perspective on the interplay between patients, family members, and physicians, cohort studies are needed. Meanwhile, clinicians should validate patients and family members considering refraining from aggressive end-of-life care and explore their motives.Clinical trial registrationhttps://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00022837, identifier DRKS00022837.
Gesehen am 07.12.2022